2023
DOI: 10.1101/2023.02.22.23286149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cerebellum and cognitive function: anatomical evidence from a transdiagnostic sample

Abstract: Introduction: The cerebellum, most known for its role in motor control, exerts a key role in cognition. Multiple lines of evidence across human functional, lesion and animal data point to a role of the cerebellum, in particular of Crus I, Crus II and Lobule VIIB, in cognitive function. However, whether cerebellar substrates pertaining to distinct facets of cognitive function exist is not known. Methods: We analyzed structural neuroimaging data from the Healthy Brain Network (HBN). Cerebellar parcellation was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(91 reference statements)
2
2
0
Order By: Relevance
“…Speed of processing was negatively correlated to cerebellar manifestations' severity, which is consistent with the role of the cerebellum in this ability. 13 Approximately one third of the patients exhibited episodic memory deficits, mainly resulting from impaired executive control of memory, which is consistent with the initial description of the CCAS 11 and usually observed in frontostriatal dysfunction. 14 However, three patients exhibited a different pattern with significant storage deficits, suggesting damage or dysfunction of the hippocampus or temporal cortex.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Speed of processing was negatively correlated to cerebellar manifestations' severity, which is consistent with the role of the cerebellum in this ability. 13 Approximately one third of the patients exhibited episodic memory deficits, mainly resulting from impaired executive control of memory, which is consistent with the initial description of the CCAS 11 and usually observed in frontostriatal dysfunction. 14 However, three patients exhibited a different pattern with significant storage deficits, suggesting damage or dysfunction of the hippocampus or temporal cortex.…”
Section: Discussionsupporting
confidence: 83%
“…Results from the comprehensive neuropsychological test battery confirm that attention/working memory and executive function were the most affected domains. Speed of processing was negatively correlated to cerebellar manifestations' severity, which is consistent with the role of the cerebellum in this ability 13 . Approximately one third of the patients exhibited episodic memory deficits, mainly resulting from impaired executive control of memory, which is consistent with the initial description of the CCAS 11 and usually observed in frontostriatal dysfunction 14 .…”
Section: Discussionsupporting
confidence: 81%
“…Bègue and co-workers used canonical correlation analyses to link cerebellar grey matter volume to cognitive functioning. They proposed two maps: one associated with cognitive flexibility, processing speed and working memory (Crus II and Lobule X) and the other with working memory (Crus I and Lobule VI), both linked also to working memory (Bègue et al, 2023). While cerebellar volume reduction is the 10.3389/fncel.…”
Section: Cerebellar Structural and Functional Abnormalities And Ciasmentioning
confidence: 99%
“…of studies have demonstrated that nearly the entire cerebellum is involved in cognitive function (Figure 1). [26][27][28][29][30][31][32] Cerebellar activation is associated with various tasks, including those related to working memory, learning, attention, and executive control. 9,33 In particular, Crus I and Crus II contribute to parallel cortico-cerebellar circuits that regulate executive control, salience detection, and scene memory/self-reflection.…”
Section: Clinical Manifestations Linking Cerebellum To Admentioning
confidence: 99%